Genetic connectivity of lionfish (Pterois volitans) in marine protected areas of the Gulf of Mexico and Caribbean Sea - Guzmán‐Méndez, Irán A.; Rivera‐Madrid, Renata; Planes, Serge; Boissin, Emilie; Cróquer, Aldo; Agudo-Adriani, Esteban; González‐Gándara, Carlos; Perez‐España, Horacio; Giro‐Petersen, Ana; Luque, Jenny; García‐Rivas, María del C.; Aguilar‐Espinosa, Margarita; et al. (Ecology and evolution, 2020)
Lionfish (Pterois volitans) have rapidly invaded the tropical Atlantic and spread across the wider Caribbean in a relatively short period of time. Because of its high invasion capacity, we used it as a model to identify the connectivity among nine marine protected areas (MPAs) situated in four countries in the Gulf of Mexico and the Caribbean Sea. This study provides evidence of local genetic differentiation of P. volitans in the Gulf of Mexico and the Caribbean Sea. A total of 475 lionfish samples were characterized with 12 microsatellites, with 6–20 alleles per locus. Departures from Hardy–Weinberg equilibrium (HWE) were found in 10 of the 12 loci, all caused by heterozygous excess. Moderate genetic differentiation was observed between Chiriviche, Venezuela and Xcalak, México localities (FST = 0.012), and between the Los Roques and the Veracruz (FST = 0.074) sites. STRUCTURE analysis found that four genetic entities best fit our data. A unique genetic group in the Gulf of Mexico may imply that the lionfish invasion unfolded both in a counterclockwise manner in the Gulf of Mexico. In spite of the notable dispersion of P. volitans, our results show some genetic structure, as do other noninvasive Caribbean fish species, suggesting that the connectivity in some MPAs analyzed in the Caribbean is limited and caused by only a few source individuals with subsequent genetic drift leading to local genetic differentiation. This indicates that P. volitans dispersion could be caused by mesoscale phenomena, which produce stochastic connectivity pulses. Due to the isolation of some MPAs from others, these findings may hold a promise for local short‐term control of by means of intensive fishing, even in MPAs, and may have regional long‐term effects. Our findings demonstrate that there is genetic differentiation at local and regional scales.We suggest that the colonization of each geographic area has been temporary pulses, probably caused by mesoscale phenomena, and intensified with the presence of self‐recruitment. The genetic diversity of Pterois volitans in the Gulf and the Caribbean showed that the number of organisms that originated the invasion was much higher than the one mentioned in the literature.